Perancangan Desain Interface E-Learning Berbasis Web dengan Pendekatan Kansei Engineering - Indra Griha Tofik Isa; Ana Hadiana (Maranatha University Press, 2017)
Human Computer Interaction is how to make a good communication between computer and user. In its development, not only focused on usability aspect and technical, but also how to make product more persuasive in psychological aspect. Kansei Engineering (KE) comes to fulfill the product designing which involves userâ€™s psychological or affective factors. There are several KE method in designing product, one of them is Kansei Engineering Type I which is involved in this research. The purpose in this research is to know some psychological factors related with web based interface e-learning design and how to make web based e-learning guideline matrix recommendation by Kansei Engineering Type I. Â 10 web based e-learning specimens, 20 Kansei Words and 30 participants are involved in the research.